Gadget Use and Eye Fatigue on Students During COVID-19 Pandemic - Buenita Sinurat; Perry Boy Chandra Siahaan; Putranto Manalu; Hartono Hartono; Gunarto Sinaga (STIKes Hang Tuah Pekanbaru, 2022)
The increasing intensity of gadget use in online learning during the COVID-19 pandemic impacts increasing eye fatigue complaints in students. This study analyzes the relationship between gadget use and eye fatigue complaints in college students during the COVID-19 pandemic. This study is a quantitative study using a cross-sectional design involving a sample of 171 students of the Public Health Study Program of the University of Prima Indonesia. The sampling technique used purposive sampling with inclusion criteria, namely, students in semester 2 to semester 8. The data were analyzed using the Chi-Square test and multiple logistic regression tests. The results of statistical tests using the Chi-Square test showed that a history of eye disease (0.000), the type of gadget used (0.000), the position of using the gadget (0.020), the distance of using the gadget (0.000), and the duration of using the gadget (0.000) were associated with complaints of fatigue. eye. Age (0.325) and gender (0.973) had no significant effect. This study concludes that a history of eye disease, more than 1 type of gadget use, long-term use of gadgets, poor body position, and too close a distance are triggers for eye fatigue complaints. The most dominant factor in this study was the use of more than 1 type of gadget (p= 0.001; PR= 0.098, 95%CI = 0.025 - 0.381). To reduce the negative effects of using gadgets for a long time, students are expected to rest regularly and adjust the position and distance of the gadget screen.